#TITLE_ALTERNATIVE# - (NIM 124 04 015); Pembimbing : Wahyu Trioyoso, Ph.D., SUJONO
Preconditioning data optimum seismik is very required for advance prosessing for example to analyse hydrocarbon and analysis AVO(Amplitude versus Offset). Data Quality seismik that either determined when prosessing good and accurate data. Method seismik reflection have limited frequency in consequence, has been according to next if reflection from a source is assumed as a dot. Method Common Reflection surface develop by (Muler, 1998; Hubral, 1998; Hocht, 1998; Jager, 1998) where wave source in assumption as a line at 2D and a area at 3D. Line or this luasan are known as fresnel zone. By exploit information from respon reflection around dot ZO as long as this fresnel zone (multicoverage data), then will be got a surface stacking for every ZO point. By undertaking addition as long as surface line stacking are referred, for then put it in dot ZO so it's got section stacking CRS. In this study writer tries compare to conventional method and method CRS from synthetic data and data real. Goals Area are identfy as gas that processed in konvensioanal and CRS until get preconditioning data better gather PSTM to conduct Analisis AVO. From experiment that conducted in the reality data that processed with method CRS gives data better PSTM gather for example : have s/n high, preserve amplitude until informational that more precisely in Analisis AVO.